POSITIONING A SMALL CARRIER IN A MARKET DOMINATED BY LARGE PLAYERS: BUILDING A MICROSTRATEGY - Liestiev, Yevhen (European Journal of Interdisciplinary Issues, 2025)
The aim of the article is to improve methodological approaches to developing a microstrategy for positioning a small carrier in the freight market to ensure a competitive advantage in the conditions of dominance of large logistics operators. The study uses systems analysis for market segmentation, mathematical modeling of the nonlinear dependence of demand on resource capacity, as well as statistical methods for forecasting demand, taking into account cyclical fluctuations. Methods of route optimization, analysis of operational efficiency, modeling of flexible logistics scenarios and assessment of client interactions are applied. Analytical models are based on the principles of maximizing the expected operational effect and taking into account the probabilities of demand deviations. A microstrategy is proposed that focuses on localized market segments (peripheral areas, agricultural zones, industrial parks), where small carriers have an advantage due to speed, flexibility and personalization. A structural and functional transportation management model has been developed, including route optimization, flexible planning, dynamic pricing, a hybrid model of regular and one-time transportation, as well as individualized agreements with customers. The dependence of demand on operating activity with three zones has been established: insensitivity, effective growth, and saturation. Adaptive logistics tools have been proposed, in particular, a portfolio of customers with opposite cycles and capacity reservation, to smooth out seasonal fluctuations. An analytical model of a forecast production program takes into account resource constraints and ensures a balance between demand and capacity. The concept of “dynamic demand” has been developed, which allows a small carrier to actively influence the volume of orders through adaptive mechanisms. A unique positioning model has been proposed that integrates speed, flexibility, and personalization as key competitive advantages of small enterprises in logistics. The study deepens the understanding of the competitive strategies of small carriers, clarifying the role of market segmentation, adaptive logistics and individualization in conditions of limited resources, which contributes to the development of the theory of logistics management. The proposed tools (route optimization, flexible planning, dynamic pricing, customer base diversification, short-term contracts) allow small carriers to increase operational efficiency, stabilize cash flows, minimize the impact of seasonality and ensure the sustainability of the business model. The implementation of microstrategy contributes to the formation of customer loyalty and the creation of long-term partnerships, which increases competitiveness at the local level.